ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEMISKINAN DI KALIMANTAN TIMUR PADA ERA DESENTRALISASI FISKAL TAHUN 2014-2020 - Brian Jordi; Wiguna, Atu Bagus (Journal of Development Economic and Social Studies, 2022)
Poverty is a condition where income is unable to meet basic needs, so it is less able to guarantee survival. This study aims to determine the effect of natural resources, fiscal decentralization, human development index, and labor force participation rate on poverty in East Kalimantan Province. The object of this research is 10 regencies/cities in East Kalimantan in 2014-2020, while the data analysis used is panel data regression which produces the best model, namely the Random Effect Model (REM). The results showed that the variables of natural resources, human development index, and labor force participation rate had a positive and insignificant effect on poverty in East Kalimantan. in contrast, the variable of fiscal decentralization had a negative and significant impact on poverty in East Kalimantan.